English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

as in 2x - 6 = 7
5

2007-06-08 02:40:12 · 12 answers · asked by brandoleigh 3 in Science & Mathematics Mathematics

sorry 2x -6 divided by 5 and then equals 7 altogether

2007-06-08 02:41:16 · update #1

12 answers

(2x-6)/5=7 (Multiply both sides by 5)

2x-6=35
2x=35+6
2x=41
x=20.5

2007-06-08 02:44:43 · answer #1 · answered by nivik 3 · 0 1

If it's 2x minus 6 over 5 = 7
first add 6/5 to both sides giving you: 2x = 7 + 6/5
then divide both sides by 2 giving you x = (7 + 6/5)/2
or x = 4.1

if it's 2x minus 6 all over 5 = 7
first multiply both sides by 5 giving you 2x - 6 = 7 X 5
or 2x - 6 = 35
next add 6 to both sides giving you 2x = 35 + 6
or 2x = 41
then divide both sides by 2 giving you x= 41/2
or x = 20.5

2007-06-08 02:55:21 · answer #2 · answered by James S 2 · 0 1

Multiply both sides by 5, which would get rid of the 5 under (2x-6).

So now 2x - 6 = 35.

Then add six to both sides, which would get rid of the 6 on the left.

So now 2x = 41

Now divide both sides by 2, which would get rid of the 2 on the left.

so now x = 20.5

Remember that when solving equations you do the same thing on both sides, with your goal being to isolate the letter.

2007-06-08 02:47:34 · answer #3 · answered by Christine L 2 · 0 1

Hi,

First off, multiply both sides by 5 in order to get rid of the divided by 5 portion on the left hand side of the equation. So, you would then get:

2x - 6 = 35

Now add 6 to both sides . . .

2x = 41

Then divide by 2

x = 41 / 2 or 20.5

I hope that helps you out! Please let me know if you have any other questions!

Sincerely,

Andrew

2007-06-08 03:11:33 · answer #4 · answered by The VC 06 7 · 0 0

It's already solved but mind that Anya's solution is not correct as the parentheses are in the wrong places. Using parentheses the whole thing should like:
(2x-6)/5=7 this leads to the solution 20.5
while (2x-6/5)=7 gives
2x-1.2=7
2x=8.2
x=4.1 - but someone else has calculated that already.

2007-06-08 03:20:23 · answer #5 · answered by Martin S 7 · 0 1

I'll assume that the entire 2x-6 is divided by 5 as opposed to it being 2x - six fifths.

The key here is to isolate x.

So, according to my assumption, multiply both sides by 5. That gives you:

2x-6=35 Now, add 6 to both sides and you get
2x=41 Divide by 2, and you get:
x=41/2

2007-06-08 02:48:20 · answer #6 · answered by Anonymous · 0 2

here is the long method for you to understand

2x-6/5=7

5(2x-6/5)=7x5

2x-6=35

6+(2x-6)=35+6

2x=41

1/2(2x)=41(1/2)

x=20.5

remember what you did on one side shall be done to the other side too... try all the ways to leave the variable x alone in one side...

hope this helps.. ^^

2007-06-08 03:02:15 · answer #7 · answered by Anya 2 · 0 1

2x-6/5=7

1st divide both sides by 5 to take away fraction- you are left with 2x-6=35

2nd add six to both sides- you're left with
2x=41

3rd divide both sides by 2 to get variable isolated

x=41 or 20.5 is your final answer

2007-06-08 15:15:37 · answer #8 · answered by N 3 · 0 0

2x-6=35
2x=41
x=41/2
x=20.5
if 2x-6 the whole thing is divided by 5

2007-06-08 02:44:57 · answer #9 · answered by Anonymous · 0 1

(2x - 6 ) / 5 = 7
2x - 6 = 35
2x = 35 +6
2x = 41
x = 41 / 2
= 20.5

2007-06-08 02:46:03 · answer #10 · answered by Nana Diyana 1 · 0 1

fedest.com, questions and answers